2014
DOI: 10.1103/physrevd.89.055009
|View full text |Cite
|
Sign up to set email alerts
|

Large neutrino magnetic dipole moments in MSSM extensions

Abstract: An analysis of the Dirac neutrino magnetic moment with standard model interactions gives

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…The Matsubara Green function can be derived from expressions (10), (11) by the substitution (12) where the imaginary time parameter is (13) Without loss of generality, we consider the case of a charge-symmetric electron-positron plasma when the chemical potential is zero. When necessary, the general case can always be reconstructed from that considered here by introducing the chemical potential into the corresponding distribution function.…”
Section: Contribution From a Charged Weak Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Matsubara Green function can be derived from expressions (10), (11) by the substitution (12) where the imaginary time parameter is (13) Without loss of generality, we consider the case of a charge-symmetric electron-positron plasma when the chemical potential is zero. When necessary, the general case can always be reconstructed from that considered here by introducing the chemical potential into the corresponding distribution function.…”
Section: Contribution From a Charged Weak Currentmentioning
confidence: 99%
“…For astrophysics and the physics of neutrinos, the "consistency" of the small mass and the large magnetic moment of the neutrino remains an important problem [11][12][13]. In the minimally extended standard Weinberg-Salam-Glashow model, the static anomalous magnetic moment of the Dirac neutrino with mass m ν is defined as [14] (1)…”
Section: Introductionmentioning
confidence: 99%
“…That is why in well-studied models without such a mechanism, like the left-right symmetric model [22] and the supersymmetric model [23], the NMM predictions are far from being detected in next-generation experiments. On the other hand, a recent parameter study in the framework of the minimal supersymmetric model found room for large NMM [24], but does not solve the fine-tuning problem.…”
Section: Jhep07(2017)139mentioning
confidence: 99%
“…Further, vectorlike multiplets arise in a variety of settings such as in grand unified models and in string and D brane models [8,10,11]. Vectorlike generations have been considered by several authors since their discovery would constitute new physics (see, e.g., [9,10,11,12,13,14,15,16,17,18,19,20,21,22]). Such models have new sources of CP violation and thus can generate substantial size dipole operators.…”
Section: Introductionmentioning
confidence: 99%